Pengembangan Kartu UNO Math dengan Google Slide dalam Model TGT terhadap Kemampuan Penalaran Matematis - Dian Fitri Fransiska; Fadhilah Rahmawati Rahmawati; Megita Dwi Pamungkas (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
The purpose of this study was to develop UNO Math Cards using Google Slides with validity, practicality, and effectiveness in the TGT learning model to enhance student’s mathematical reasoning ability. This research employed RD (Research and Development) with the 4D model (Define, Design, Development, and Disseminate) involving 32 students in the experimental class. The findings revealed that the product achieved a validity score of 88.1%, categorized as very valid. A practicality score of 86.25%, indicating that the media is practical to use. An efectiveness value of 0.6603, showing that the media is effective in improving students’ mathematical reasoning ability. Therefore, the UNO Math Cards using Google Slides are declared valid, practical, and effective for use in the TGT learning model to support students’ mathematical reasoning skills